2008
DOI: 10.1249/mss.0b013e3181593e02
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Psychological Effects of Caffeine Ingestion in 40-km Cycling Performance

Abstract: Our data support the ergogenic efficacy of caffeine but suggest that both positive and negative expectations impact performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
112
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(124 citation statements)
references
References 19 publications
7
112
3
2
Order By: Relevance
“…Another study showed that it is possible to modulate the subject expectations, according a dose-response paradigm (39). Similar placebo effects were found in other studies (38,132,230,232). Interestingly, if an athlete holds negative beliefs about the ergogenic aid just received, a nocebo effect may occur so that the following performance drops as well (37,261).…”
Section: Moving From the Clinical Setting To Physical Performancesupporting
confidence: 65%
“…Another study showed that it is possible to modulate the subject expectations, according a dose-response paradigm (39). Similar placebo effects were found in other studies (38,132,230,232). Interestingly, if an athlete holds negative beliefs about the ergogenic aid just received, a nocebo effect may occur so that the following performance drops as well (37,261).…”
Section: Moving From the Clinical Setting To Physical Performancesupporting
confidence: 65%
“…Importantly, caffeine can reduce perception of effort and exercise-induced muscle pain even at relatively low doses [38] and in habitual high caffeine consumers [39]. We should also consider that, in real-life applications, the efficacy of caffeine would be enhanced by its placebo effect [40] and associated changes in motorrelated cortical activity [41]. In addition to these positive psychobiological effects, caffeine can also create a greater energy deficit after exercise [37] thus helping with the prevention and treatment of obesity.…”
Section: Caffeine and Other Psychoactive Drugsmentioning
confidence: 99%
“…There are also, many speculative anecdotal examples of what may be legitimate placebo effects (12). Expectations of substance-specific effects seem to trigger many physiological and psychological reactions (30), independent of the substance given (22,29,63). Within this type of expectancy manipulation, the deception element of the methodology is known, with the participant's acknowledgement prior to the investigation, of a substance's possible effects.…”
Section: Placebosmentioning
confidence: 99%